Effect of olive leaf extract on the quality of Cantal cheese - Ines Tarchi; Mohamed Bouaziz; Zuhaib F. Bhat; Abderrahmane Aït-Kaddour (Food Chemistry: X)
This study aimed to evaluate the impact of olive leaf extract (OLE) on the quality of Cantal cheese. The cheeses were fortified with different concentrations (Control, 1, 2, and 3 %) of OLE and analysed for quality during storage. The cheeses were evaluated on days 1, 28, and 63 for physicochemical, compositional, textural, rheological parameters, colour, microbiological analysis, and antioxidant activity. The MIR and fluorescence spectroscopies were used to study the changes in the cheese molecular structure. A positive impact of OLE was observed on the antioxidant capacity. A mild inhibitory effect was observed against some beneficial bacteria (such as Lactococcus and Lactobacillus), while a strong inhibitory effect was found against pathogen microorganisms. No negative impact was found on the texture and chemical composition. Significant colour and structural changes were observed. The results indicate the potential of OLE to be used as bioactive ingredient to improve the quality of cheese.